2001
DOI: 10.1002/1522-2683(200111)22:19<4281::aid-elps4281>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis and electrochromatography of pesticides and metabolites

Abstract: Synthetic pesticides are important chemicals since they are widely used to control many types of weeds, insects, and other pests in a wide variety of agricultural and nonagricultural settings. This review article is aimed at describing the recent progress made in capillary electrophoresis (CE) and capillary electrochromatography (CEC) of pesticides and metabolites. The various electrophoretic systems and detection schemes that were introduced during the period extending from the second half of 1999 to the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Although conventional analytical techniques, especially chromatography and electrophoresis, offer efficient and sensitive detection of extremely low amounts of pesticides in various matrices [2,3], there are certain limitations related to complexity and time-consuming procedures of sample pre-treatment including extraction and use of organic solvents.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Although conventional analytical techniques, especially chromatography and electrophoresis, offer efficient and sensitive detection of extremely low amounts of pesticides in various matrices [2,3], there are certain limitations related to complexity and time-consuming procedures of sample pre-treatment including extraction and use of organic solvents.…”
Section: Introductionmentioning
confidence: 65%
“…The bimolecular inhibition Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/talanta (3) However, high overvoltage of direct thiocholine oxidation prevents application of ATCh in the media containing easily oxidizable compounds. Thus, the potential of thiocholine oxidation is about 680 mV on Pt electrode and 450 mV on glassy carbon.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The availability of many chiral selectors make CE an important tool for chiral analysis. [1][2][3][4][5]8,9) For example, cyclodextrins, linear polysaccharides, crown ethers, chiral surfactants, proteins, macrocyclic antibiotics, and chiral ion-pairing reagents are used as selectors. Of these selectors, cyclodextrins (CDs) and their derivatives have been most widely applied in CE for the separation of enantiomers of many compounds including agrochemicals.…”
Section: Principle Of Enantioseparation In Capillary Electrophoresismentioning
confidence: 99%
“…However, most of articles in recent reviews [1][2][3][4] have reported enantioseparation of agrochemicals in standard solution, whchi does not contain matrices, only several publications that deal with the enantioseparation of agrochemicals in real samples by using CE technique that contain complex and various matrices has been reported until now. Analytical separation methods are needed to monitor the stereoselective synthetic process used in agrochemical production, assess the enantiopurity of commercial agrochemical production, detect the various enantiomeric agrochemicals in environmental matrices and foods, and understand the discrimination of enantiomers in environmental compartments.…”
Section: Introductionmentioning
confidence: 99%